Cost-effectiveness of precision screening for esophageal cancer based on individualized risk stratification in China: Real-world evidence from the ESECC trial - Li, Fuxiao; Liu, Mengfei; Guo, Chuanhai; Xu, Ruiping; Li, Fenglei; Liu, Zhen; Pan, Yaqi; Liu, Fangfang; Liu, Ying; Cai, Hong; He, Zhonghu; Ke, Yang (Frontiers in Oncology, 2022)
Background: Conventional universal endoscopic screening with pathology-based endoscopic re-examination for esophageal squamous cell carcinoma is in need of reform in China. We established a “two-step” precision screening strategy using two risk prediction models and have evaluated the cost-effectiveness of this precision strategy compared with the traditional strategy based on a large population-level randomized controlled trial from a healthcare provider’s perspective. Methods: Four precision screening strategies with different risk cutoffs at baseline screening and endoscopic surveillance were constructed, and then compared with traditional strategy through modeling using subjects from the screening cohort of the ESECC (Endoscopic Screening for Esophageal Cancer in China) trial. Total screening costs and the number of SDA (severe dysplasia and above in lesions of the esophagus) cases were obtained to calculate the average screening cost per SDA detected, the incremental cost-effectiveness ratio (ICER) and protection rates. Sensitivity analysis was conducted to evaluate uncertainties. Results: Compared to traditional strategy, all precision screening strategies have much lower average costs for detection of one SDA case ($7,148~$11,537 vs. $14,944). In addition, precision strategies 1&2 (strategies 1,2,3,4 described below) achieved higher effectiveness (143~150 vs. 136) and higher protection rates (87.7%~92.0% vs. 83.4%) at lower cost ($1,649,727~$1,672,221 vs. $2,032,386), generating negative ICERs (-$54,666/SDA~-$25,726/SDA) when compared to the traditional strategy. The optimal strategies within different willingness-to-pay (WTP) ranges were all precision screening strategies, and higher model sensitivities were adopted as WTP increased. Conclusions: Precision screening strategy for esophageal cancer based on risk stratification is more cost-effective than use of traditional screening strategy and has practical implications for esophageal cancer screening programs in China.